REFORMULASI PENGATURAN PEMBANGUNAN JALAN DESA KABUPATEN MALANG - Avicenna M Saniputera (Legal Spirit, 2019)
The administration of government in all lines has a high level of complexity. In the discourse of the state of law, all such implementation must be based on definite legal rules, or known as due process of law. The prerequisites that must be met in the rule of law, are certainty and harmonization. Certainty means not multiple interpretations, and harmonious, does not collide with other arrangements. Apparently these aspects were not fulfilled in the Law governing village roads. There were two institutions that were obliged to implement them, not to mention the standard distribution, which were village roads, and Malang district roads. For this reason, this study discusses: First, How is the juridical analysis and the impact of regulating the authority of organizing village roads in Malang regency in terms of the Regional Government Law, the Village Law and the Road Law? Second, how are the efforts to reform the village road development arrangements in the future that meet the elements of legal certainty and in accordance with the direction of regional development in Malang Regency? This research uses normative legal research, with the approach of statutory and conceptual regulations.Key words: Reformulation, Development, Village Road, Malang Regency